Water Supply and Sanitation in Central African Republic : Turning Finance into Services for 2015 and Beyond - World Bank (Washington, DC, 2014)
The African Ministers' Council on Water (AMCOW) commissioned the production of a second round of country status overviews (CSOs) to better understands what underpins progress in water supply and sanitation (WSS) and what its member governments can do to accelerate that progress across countries in Sub-Saharan Africa (SSA). AMCOW delegated this task to the World Bank's Water and Sanitation Program and the African Development Bank who are implementing it in close partnership with United Nations Children's Fund (UNICEF) and World Health Organization (WHO) in over 30 countries across SSA. This second CSO report has been produced in collaboration with the Government of the Central African Republic and other stakeholders during 2009-10. The analysis aims to help countries assess their own service delivery pathways for turning finance into water supply and sanitation services in each of four subsectors: rural and urban water supply, and rural and urban sanitation and hygiene. The second CSO analysis has three main components: a review of past coverage; a costing model to assess the adequacy of future investments; and a scorecard which allows diagnosis of particular bottlenecks along the service delivery pathway. The second CSO's contribution is to answer not only whether past trends and future finance are sufficient to meet sector targets, but what specific issues need to be addressed to ensure finance is effectively turned into accelerated coverage in water supply and sanitation. In this spirit, specific priority actions have been identified through consultation. A synthesis report, available separately, presents best practice and shared learning to help realize these priority actions.